ENT 530 Social Media Portfolio: Skindessert Exclusive Perfume / Ain Nur Farzanah Ahmad Mujahid - Ahmad Mujahid, Ain Nur Farzanah (2020)
Inspired perfume by Skindessert Exclusive Perfume actually a combination of fragrant essential oils or aromatic compounds, fixatives and solvents, typically in liquid forms that used to provide a pleasant fragrance to the human body, food, objects and living spaces. The skindessert perfume comes with three level, which are for men, women and also unisex. The smell truly make everyone falling in love at the first spray of fragrances. It such a delightful, fresh and lovely perfumes ever in the world. The reason to promote these perfume is because there a lot of people needs a good smell to make themselves feel so lovely and energetic for their daily life. This product and services not only focused on the smell segments. It also focused on benefits itself to their consumer. It because of the fragrances can be divided into variety of scent that can gives different perspective towards other people based on the perfume that have been choose. As your perfumes is your message and your scented slogan.